2007
DOI: 10.24200/squjs.vol12iss2pp101-120
|View full text |Cite
|
Sign up to set email alerts
|

Review of Health Information Systems in Oman

Abstract: This paper is a review of Oman's major Health Information Systems (HISs) and their enabling technologies. The work assesses the scope, functionality, security, and interoperability of the used systems. The review aids in achieving the objectives of HIS systems of improving the global quality of health care, attaining increased coordination between health care providers and consumers, promoting the use of guidelines and policies, and improving the speed of simultaneous access and distribution of medicalrecords … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…A few studies reported thateffective e-health investment did not result in better quality and improved productivity but it freed up capacity and enabled greater access (Kaye, Kokia, Shalev, Idar, & Chinitz, 2010).From the perspective of the doctors, health IT (particularly EHR) was found to be time-consuming. The doctors were too busy to deal with it and they feared that it would depersonalize healthcare and would interfere with their rapport with their patient [5] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies reported thateffective e-health investment did not result in better quality and improved productivity but it freed up capacity and enabled greater access (Kaye, Kokia, Shalev, Idar, & Chinitz, 2010).From the perspective of the doctors, health IT (particularly EHR) was found to be time-consuming. The doctors were too busy to deal with it and they feared that it would depersonalize healthcare and would interfere with their rapport with their patient [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Medical Audit was found to be vital for the measurement of the quality of care given to the practice population (Elhadi, et al, 2007). Medical audit required standard setting, data collection, comparison with standards, review of data and standards [6] .…”
Section: Introductionmentioning
confidence: 99%
“…In the second phase, all current HIS systems were to become inter-connected by the end of 2007 with a middleware called e-referral engine. In phase III (final), the national repository of electronic health records was created by the end of 2010 ( 19 , 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…The system was isolated physically from the internet and it did not allow the use of removable storage such as USB memory and CDs within the Health Net. Medical Audit was found to be vital for the measurement of the quality of care given to the practice population (Elhadi, et al, 2007). Medical audit required standard setting, data collection, comparison with standards, review of data and standards.…”
Section: Review Of Literaturementioning
confidence: 99%